Long-lasting potentiation of hippocampal synaptic transmission by direct cortical input is mediated via endocannabinoids - Xu, Jian-Yi (Blackwell Science Inc, 2012)
Hippocampal CA1 pyramidal neurons receive sensory inputs from the entorhinal cortex directly through the perforant path (PP) and indirectly through Schaffer collaterals (SC). Direct cortical inputs to CA1 pyramidal neurons through the PP provide instructive signals for hippocampal long-term synaptic plasticity. However, the molecules conveying synaptic signalling in this new form of heterosynaptic plasticity remain unclear. Endocannabinoids, important endogenous signalling mediators, modulate synaptic efficacy primarily through inhibition of GABAergic or glutamatergic synaptic transmission via presynaptically expressed CB1 receptors. Here, we report that pairing of direct and indirect cortical inputs to CA1 pyramidal neurons resulted in a long-lasting potentiation of synaptic responses at SC synapses, but not at the PP. The pairing-potentiated synaptic transmission at the SC was accompanied by a reduced ratio of paired-pulse facilitation (PPR). Enhanced synaptic response at the SC by pairing of PP–SC stimuli is Ca(2+) dependent and requires the presence of functional GABAergic and glutamatergic synaptic transmissions and activation of group I metabotropic glutamate receptors. Pharmacological inhibition or genetic deletion of the CB1 receptor eliminated the pairing-induced long-term synaptic plasticity and decreased PPR at the SC. The potentiation induced by pairing of PP–SC stimuli primarily is the glutamatergic synaptic transmission. While the pairing-induced long-lasting potentiation of synaptic response was blocked by inhibitors for diacylglycerol lipase (DGL), which biosynthesizes 2-AG, inhibition of monoacylglycerol lipase (MAGL), which metabolizes 2-AG, facilitated the potentiation at SC synapses by pairing of weak PP–SC stimuli. Our results suggest that 2-AG functions as a signalling mediator tuning synaptic efficacy at the proximal synapses of hippocampal CA1 pyramidal neurons while direct and indirect cortical inputs to the same neurons are spatiotemporally primed.